Current opinions on tendinopathy - Kaux, J.-F.; Forthomme, B.; Le Goff, S.; Crielaard, J.-M.; Croisier, J.-L. (Journal of Sports Science & Medicine, 2011)
Tendinopathy is characterized by pain in the tendon and impaired performance sometimes associated with swelling of the tendon. Its diagnosis is usually clinical but ultrasonography and magnetic resonance imaging can refine the diagnosis. Tendinopathy is highly prevalent and is one of the most frequently self reported musculoskeletal diseases in physical workers and sports people. Nevertheless, it is very difficult to carry out general epidemiologic studies on tendinopathy because of the varying sports cultures and sports habits in different countries. The aetiology of tendinopathy seems to be multi-factorial, involving intrinsic and extrinsic factors. The role of inflammation is still debated but the absence of inflammatory cells does not mean that inflammatory mediators are not implicated. Different theories have been advanced to explain pain and chronicity mechanisms, but these mechanisms remain largely unknown. "Conventional" treatments are generally employed empirically to fight pain and inflammation but they do not modify the histological structure of the tendon. However, these treatments are not completely satisfactory and the recurrence of symptoms is common. Currently, eccentric training remains the treatment of choice for tendinopathy, even though some studies are contradictory. Moreover, many interesting new treatments are now being developed to treat tendinopathy, but there is little evidence to support their use in clinical practice.